Lyotropic Lamellar Phase Formed from Monolayered θ‐Shaped Carborane‐Cage Amphiphiles1. Issue 46 (4th November 2013) - Brusselle, Damien; Bauduin, Pierre; Girard, Luc; Zaulet, Adnana; Viñas, Clara; Teixidor, Francesc; Ly, Isabelle; Diat, Olivier
<x xml:space="preserve">Abstract</x> B in phase: Lyotropic lamellar phases can not only be formed from alkyl‐chain‐based surfactants with a well‐defined amphiphilic structure, now they can be obtained from metallacarborane clusters, described as θ‐shaped amphiphiles. The lamellae formed are unique as they have a monomolecular thickness.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>